2019
DOI: 10.1038/s41467-019-10800-1
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of extrasynaptic GABAA alpha 5 receptors in the ventral hippocampus normalizes physiological and behavioral deficits in a circuit specific manner

Abstract: Hippocampal hyperactivity is correlated with psychosis in schizophrenia patients and likely attributable to deficits in GABAergic signaling. Here we attempt to reverse this deficit by overexpression of the α5-GABA A receptor within the ventral hippocampus (vHipp). Indeed, this is sufficient to normalize vHipp activity and downstream alterations in dopamine neuron function in the MAM rodent model. This approach also attenuated behavioral deficits in cognitive flexibility. To understand th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(86 citation statements)
references
References 67 publications
(99 reference statements)
6
69
0
Order By: Relevance
“…4e ). We have also selected α5-containing GABA A Rs (α5β2γ2) as a representative for an extrasynaptic GABA A R 29 , 30 , and examined the effect of GABARAP on this type of GABA A R. GABARAP also significantly increased the GABA A R-mediated current as induced by 1 mM GABA (Supplementary Fig. 5a ), suggesting that γ2 containing extrasynaptic GABA A Rs are also sensitive to regulation by GABARAP.…”
Section: Resultsmentioning
confidence: 99%
“…4e ). We have also selected α5-containing GABA A Rs (α5β2γ2) as a representative for an extrasynaptic GABA A R 29 , 30 , and examined the effect of GABARAP on this type of GABA A R. GABARAP also significantly increased the GABA A R-mediated current as induced by 1 mM GABA (Supplementary Fig. 5a ), suggesting that γ2 containing extrasynaptic GABA A Rs are also sensitive to regulation by GABARAP.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown the involvement of a5 subunits in tonic inhibitory currents recorded in the hippocampus and neocortex (Caraiscos et al, 2004;Jacob, 2019). Pharmacological or genetic manipulation of a5 activity can produce significant modulation of learning and cognitive ability (Braudeau et al, 2011;Collinson et al, 2002;Donegan et al, 2019;Magnin et al, 2019). Altered a5 expression has also been linked to neuropsychiatric disorders, and a5 modulators may have antidepressant actions (Carreno et al, 2020;Prevot et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst this supports a link between α5-GABA A Rs dysregulation and the clinical expression of the disorder, the direction of the association is not consistent with a simple model of α5-GABA A Rs hypofunction leading to hippocampal overactivity and symptoms. It was recently shown, using a viral-mediated gene transfer, that an increase in the expression of α5-GABA A Rs normalizes VTA dopamine cell population activity [71]. Thus, one explanation that could account for both the lower [11C] Ro15-4513 binding in patients and a positive correlation with symptoms is that low α5-GABA A R levels are a vulnerability factor but that once the disorder develops there is a compensatory increase in α5-GABA A R levels in response to dysregulation of other systems.…”
Section: Strengths and Limitationsmentioning
confidence: 99%